Analisis Penerapan Manajemen Konflik untuk Mengidentifikasi Peningkatan Kinerja Karyawan Distribusi Gas - Wahyu Andriansyah Naibaho; Annio Indah Lestari Nasution; Muhammad Ikhsan Harahap (SAFE-Network, 2023)
Conflict management is a potential approach to the process of solving a problem. This process leads to forms of communication from actors and outsiders. Problems are solved to identify problems that occur in conflicts between people due to differences in culture, position, role, status, and hierarchical levels. The problem in this study is that the quantity and quality of employees are not in accordance with the target because there are several problems/conflicts that occur in the company environment. The conflict that occurs is between employees and employees and employees with superiors. The impact on the conflict results in the distribution of gas which is channeled to the bases. The purpose of this study is to identify conflicts that occur by applying conflict management to improve employee performance at PT. Sintora Putra Gasindo. The method used is quantitative research with as many as 20 data sources. The data collection technique uses instruments in a quisoner. The data analysis method used is linear regression analysis. The results of data analysis show that the termination coefficient (Adjusted R Square) is 0.862. This value indicates that simultaneous conflict management contributes 83% to employee performance, while 17% is influenced by variables not examined. 0.929. Consistent value of conflict management on employee performance by analysis of Ttable 0.4227 and Tcount 10.609 coefficient of termination. These results conclude that the independent variable has a positive effect on the dependent variable, so that the conflict management carried out at PT.Sintora Putra Gasindo has a positive effect on employee performance.